1992
DOI: 10.1042/bj2810163
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic action of lysophosphatidic acid and phosphatidic acid on fibroblasts. Dependence on acyl-chain length and inhibition by suramin

Abstract: Lysophosphatidic acid (LPA) is a naturally occurring phospholipid with growth-factor-like activities [van Corven, Groenink, Jalink, Eichholtz & Moolenaar (1989) Cell 45, 45-54]. We have examined various structural analogues of LPA for their ability to stimulate DNA synthesis in quiescent fibroblasts. When the acyl-chain length is varied, the rank order of mitogenic potency is: 1-oleoyl LPA congruent to 1-palmitoyl LPA greater than 1-myristoyl LPA greater than 1-lauroyl LPA greater than 1-decanoyl LPA; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
143
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(151 citation statements)
references
References 29 publications
8
143
0
Order By: Relevance
“…In support of this observation we have recently reported that PDGF but not TGF-␣ activates PLC and PLD in HSCs with a dose response similar to that for thymidine incorporation. 22 A role for this production of PA in PDGF-induced HSC proliferation is suggested by the mitogenic effect of exogenously added PA, which is consistent with its previously reported effects in rat and mouse fibroblasts, 13,14 human A431 carcinoma cells, 23 and human mesangial cells. 24 Assessing the precise contribution of PLD/PA to PDGF-induced HSC mitogenesis ideally requires specific PLD inhibitors that are currently unavailable.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In support of this observation we have recently reported that PDGF but not TGF-␣ activates PLC and PLD in HSCs with a dose response similar to that for thymidine incorporation. 22 A role for this production of PA in PDGF-induced HSC proliferation is suggested by the mitogenic effect of exogenously added PA, which is consistent with its previously reported effects in rat and mouse fibroblasts, 13,14 human A431 carcinoma cells, 23 and human mesangial cells. 24 Assessing the precise contribution of PLD/PA to PDGF-induced HSC mitogenesis ideally requires specific PLD inhibitors that are currently unavailable.…”
Section: Discussionsupporting
confidence: 77%
“…In fibroblast cell lines, PLD activation has been implicated in PDGF-stimulated proliferation 13 and exogenous PA has been shown to induce DNA synthesis. 13,14 However, as yet, information on this signal cascade in HSCs is restricted to a report of PDGF-induced phosphoinositide hydrolysis by PLC-␥ 15 and a more recent study reporting the interaction of PLC-␥ with focal adhesion kinase, suggesting a role in cell adhesion and migration. 16 The initial aim of the studies described in this report was, therefore, to investigate the role of the lipid-derived second messenger PA in PDGF-induced proliferation of HSCs.…”
mentioning
confidence: 99%
“…Thus photoaffinity-labelling studies with a LPA analogue have identified a binding protein of apparent molecular mass 38-40 kDa in a range of cell types, including fibroblasts [6]. Binding of LPA to this protein was inhibited by suramin, a polysulphonated naphthylurea derivative that also blocks the biological response of intact cells to LPA [7]. The initiating events in LPA-induced mitogenesis are not established, but rapid responses include inhibition of G-protein-linked adenylate cyclase [3], activation of both inositol lipid hydrolysis by phospholipase C [8] and phosphatidylcholine hydrolysis by phospholipase D [9], and activation of p2Iras [10].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that MCF-7/MDR cells contain a PtdEtn-specific PLD activity which can be selectively stimulated by PMA, sphingosine and H202* The hydrolysis of phospholipids by hormone-and phorbol ester-stimulated phospholipase D (PLD) results in the formation of phosphatidic acid [17,18]. Phosphatidic acid can serve as a messenger molecule with the potential to regulate cell growth [19][20][21][22][23][24], exocytosis [25][26][27][28][29][30], as well as other cellular processes (reviewed in [31]). In view of the emerging role of PLD in signal transduction, it is important to characterize the regulatory properties of PLD and to identify the phospholipid pools which can serve as substrates.…”
Section: Introductionmentioning
confidence: 99%